2008
DOI: 10.1111/j.1365-2222.2008.03058.x
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus infection and house dust mite exposure synergize in inducing bronchial epithelial cell interleukin‐8 release

Abstract: HRV and enzymatically active Der p I can act synergistically in the induction of bronchial epithelial IL-8 release, when HRV infection precedes or is concurrent with Der p I exposure. Such a synergy may represent an important mechanism in virus-induced asthma exacerbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 61 publications
2
40
2
Order By: Relevance
“…Allergic patients seem to clear viral infections less effectively than healthy individuals, which is in agreement with the in vitro observation of an attenuated inflammatory response of airway epithelial cells to HRV after house dust mite exposure 33. However, the functional relevance still remains unclear since allergy does not necessarily alter symptomatology or inflammation during a common cold34 (see additional information in online supplement).…”
Section: Exogenous Factors Associated With Upper Airway Inflammationsupporting
confidence: 77%
“…Allergic patients seem to clear viral infections less effectively than healthy individuals, which is in agreement with the in vitro observation of an attenuated inflammatory response of airway epithelial cells to HRV after house dust mite exposure 33. However, the functional relevance still remains unclear since allergy does not necessarily alter symptomatology or inflammation during a common cold34 (see additional information in online supplement).…”
Section: Exogenous Factors Associated With Upper Airway Inflammationsupporting
confidence: 77%
“…We showed that rhinovirus and Der f1 are synergistic with regard to the induction of IL-8, but this synergy was not observed in the case of RSV or adenovirus. Bossios et al25 described the stimulation of IL-8 release from BEAS-2B cells by the HDM Dermatophagoides pteronyssinus major allergen 1 (Der p 1), HRVs (HRV1b or HRV16), or both in different sequences. In these experiments, both rhinovirus and Der p 1 induced IL-8, IL-6, IL-29, and IP-10, while RANTES was induced only by rhinovirus.…”
Section: Discussionmentioning
confidence: 99%
“…Although many viruses have been recovered from asthmatics, rhinovirus has been most commonly (≥65%) identified in proven viral-induced asthma exacerbations in children aged 2–17 years [14]. Allergen exposure can cause disease exacerbations in children with atopic asthma [15], and viral infections and allergen exposure likely have synergistic effects on exacerbations in these children [16]. Other risk factors for asthma exacerbations include non-white race [8], younger age [11], season [12], ETS exposure [17], and outdoor air pollution [18 • ].…”
Section: Risk Factors For Asthma Exacerbationsmentioning
confidence: 99%